The role of polar organic components in dynamic crude oil adsorption on sandstones and carbonates - Piñerez Torrijos, Iván Darío; Mamonov, Aleksandr; Strand, Skule; Puntervold, Tina (CT&F - Ciencia, Tecnología y Futuro, 2020)
An appropriated wettability characterization is crucial for the successful implementation of waterflooding operations. Understanding how crude oil adsorption takes place on different mineral surfaces and how these processes impact reservoir wettability are essential aspects that can help unlock and produce large underground oil reserves. Polar organic components (POC) present in crude oil are surface-active molecules with high affinity towards mineral surfaces. POCs are quantified by the acid and base numbers (AN and BN) with units of mgKOH/g. The POC adsorption behavior is highly influenced by the type of minerals and brines present in the reservoir system. This study aims to shed light onto the most important features of oil adsorption on carbonates and sandstones mineral surfaces; particular attention is given to the role of acidic components. Therefore, outcrop sandstone and carbonate materials were used. The sandstone material contains various silicates, including quartz, Illite clay, and feldspars. The carbonate outcrop material came from the Stevns Klint quarry in Denmark and is considered a very pure calcium carbonate with minimum silicate impurities. Dynamic adsorption tests were performed at 50°C by injecting low asphaltene crude oils into core plugs, and AN and BN values of the effluent oil samples were measured and compared with the influent oil values. Furthermore, spontaneous imbibition (SI) tests were performed to assess the wettability impact of crude oil injection in oil flooded cores. The results showed that after crude oil injection, the cores became mix-wet. Confirmation of a reduction in capillary forces and a shift towards a less water-wet state was reported for both mineralogies, i.e., sandstones and carbonates. The acidic polar components had a substantial impact on carbonates wettability, while on sandstones, the experiments suggested that acidic polar components had a lower impact on wettability than that observed in the basic polar components.